GPS Operated Smart Walking Stick for Visually Impaired People - Mukherjee, D; Bhattacharyya, S; Samanta, S (International Journal of Computer Sciences and Engineering, 2025)
This paper represents the architecture and implementation of a smart self obstacle detection stick that will help to navigate the visually impaired people. This system uses GPS and voice recognition along with obstacle avoidance with the help of developed Android application. The visually impaired person issues the command and receives the direction response using audio signal, which encourage blind people to walk on the road without any help of other people. With the advancement of voice recognition system, it is now become easier to issue commands regarding directions to the visually impaired people. The blind person will provide the destination’s name as the input to the developed APP, which will plot a path to it. The app navigates the user's progress along the route and issues voice instructions for each turn.